Cloning and expression of the gene for the Avi-3 antigen of Mycobacterium avium and mapping of its epitopes. - Yamaguchi, R (1992)
The Avi-3 antigen, which is found only in Mycobacterium avium culture sonic extracts, is species specific and results in strong skin test activity in guinea pigs sensitized with heat-killed M. avium. Its gene was cloned by using a previously developed single-probe method and was sequenced. The gene encoded a 194-amino-acid polypeptide with a molecular weight of 21,500. A recombinant Avi-3 antigen expressed in Escherichia coli reacted with monoclonal and polyclonal antibodies raised against the native Avi-3 antigen. To identify epitopes on this protein for immunodiagnostic purposes, various parts of the Avi-3 antigen were expressed as beta-galactosidase fusion proteins, using pUR and pURS expression vectors. The clones screened by both antibody reactivity and T-cell proliferative activity defined fragments with coexisting B- and T-cell epitopes. A B-cell epitope (Asn-176 to Ala-186) and two T-cell epitopes (Glu-75 to Ile-86 and Arg-155 to Leu-164) were thus defined. The synthetic polymerized peptides of the T-cell epitopes were proven to elicit a delayed cutaneous hypersensitivity reaction in guinea pigs. This mapping method would be useful in the development of a subunit vaccine consisting of an immunodominant B-cell epitope linked to a T-cell epitope in the vicinity.